Organizational change in Singapore : a systems thinking approach. - Goh, Yan Ni. (2008)
In order to stay competitive, companies are undergoing massive changes. It is important to understand how companies undergo change, and how employees respond to organizational change. This study demonstrates how systems thinking adds value to a manager’s decision-making in the change management process.